Gamification and academic ability impact on students' meta-cognition and critical thinking skills - A. Abbassyakhrin; Punaji Setyosari; Siti Zubaidah; S. Sulton (Universitas Muhammadiyah Malang, 2024)
In educational settings, the metacognitive skills and critical thinking abilities of students often show room for improvement. This research aims to find out the influence of gamification methods and academic ability on metacognitive skills and critical thinking ability of high school students in Biology subjects. The independent variable in this research is the application of the Gamification method and a different method, namely the Synchronous-asynchronous method. The moderator variable is the difference in students' academic ability. The dependent variables are metacognitive and critical thinking skills. The instrument used to collect data is a test question developed to measure metacognitive and critical thinking skills. The study comprised two distinct stages. Firstly, the Dick & Carey development steps were used for development research. Secondly, a quasi-experiment was conducted using a 2x2 factorial design with 62 students divided into two groups. The research data was analyzed using the MANOVA statistical analysis technique. Based on the research results, it can be recommended that the Gamification learning method needs to be applied in the classroom with attention to the student's academic abilities.